Green Social Media Influencers: Shaping Gen Z's Green Purchase Intentions through Trust and Attitude - Faisal, Aekram; Hindardjo, Anton; Ramadhan, Rachmat (Politeknik Negeri Bandung, 2026)
This study examines the impact of Social Media Influencers (SMI) on Green Purchase Intention (GPI) among Generation Z, focusing on the mediating roles of Green Trust (GT) and Green Attitude (GA). Using a quantitative approach, data was collected from 295 Gen Z respondents in Greater Jakarta who follow eco-conscious influencers. Structural Equation Modeling and bootstrapping methods were employed. Results show SMI has no direct effect on GPI but positively influences GT and GA. GT and GA fully mediate the SMI-GPI relationship, both significantly impacting GPI. Findings emphasize the importance of building trust and positive attitudes through influencer content to boost eco-friendly product purchase intentions among Gen Z. The research contributes to understanding green consumer behavior in the digital age, offering insights for marketers targeting environmentally conscious young consumers. It also opens avenues for future research on digital marketing dynamics in promoting sustainable products to youth.